2022
DOI: 10.1021/acs.analchem.1c04402
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cysteine Chemoproteomic Coverage through Systematic Assessment of Click Chemistry Product Fragmentation

Abstract: Mass spectrometry-based chemoproteomics has enabled functional analysis and small molecule screening at thousands of cysteine residues in parallel. Widely adopted chemoproteomic sample preparation workflows rely on the use of pan cysteine-reactive probes such as iodoacetamide alkyne combined with biotinylation via copper-catalyzed azide–alkyne cycloaddition (CuAAC) or “click chemistry” for cysteine capture. Despite considerable advances in both sample preparation and analytical platforms, current techniques on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…Here we envisioned combining proximity labeling via the ultra-fast biotin ligase TurboID with cysteine chemoproteomics 11,21,[24][25][26][27][28][29][30]57,58 to enable fractionation-free capture of the subcellular cysteinome, for both residue identification and quantification of cysteine oxidation. We were inspired by recent reports of two-step capture for subcellular phosphoproteomics, in which proteins biotinylated by TurboID were first enriched on avidin resin followed by peptide-level capture of phosphopeptides 59 .…”
Section: Resultsmentioning
confidence: 99%
“…Here we envisioned combining proximity labeling via the ultra-fast biotin ligase TurboID with cysteine chemoproteomics 11,21,[24][25][26][27][28][29][30]57,58 to enable fractionation-free capture of the subcellular cysteinome, for both residue identification and quantification of cysteine oxidation. We were inspired by recent reports of two-step capture for subcellular phosphoproteomics, in which proteins biotinylated by TurboID were first enriched on avidin resin followed by peptide-level capture of phosphopeptides 59 .…”
Section: Resultsmentioning
confidence: 99%
“…Chemoproteomic studies, including our own 15,17,47,48,[53][54][55] , continue to rely on stable isotope incorporation, either through metabolic labeling or the aforementioned custom isotopically labeled capture reagents, and MS1 based quantification 10,42,[56][57][58] . These methods are widely adopted in large part due to their relatively reasonable cost, the compatibility of the resulting datasets with freely available software packages for analysis [59][60][61] , and increased data reproducibility afforded by the ability to combine 'treated' and 'control' samples early in the sample preparation workflow.…”
Section: Significant Inroads Have Already Been Made Into Realizing Th...mentioning
confidence: 99%
“…For azide source, we chose to compare ß-azidoalanine with azidolysine with the goals of determining how reducing the reagent size would impact proteomic coverage and click efficiency, together with assessing how triazole fragmentation would be impacted by choice of azide. Our prior study 55 had revealed that the gas phase fragmentation of triazole modified peptides produced signature fragment ions, with the identity, intensity, and specificity of the produced ions varying depending on the nature of the azide. Therefore, we speculated that we might observe differences in the fragmentation pattern of azidohomoalanine and azidolysine based reagents, which could be harnessed for the production of a novel isobaric labeling strategy.…”
mentioning
confidence: 99%
See 2 more Smart Citations